An assemblage of bismuth-rich, tellurium-bearing minerals in the El Quemado granitic pegmatite, Nevados de Palermo, Salta, Argentina - Marquez Zavalia, Maria Florencia (2012)
An assemblage of bismuth-rich, tellurium-bearing minerals in the El Quemado pegmatite, Salta, Argentina, represents late-stage mineralization in a spodumene-subtype, rare-element class granitic pegmatite. The minerals occur in an irregular, volumetrically minor core-margin association, dominated by fine-grained muscovite and quartz, with accessory U-rich fluornatromicrolite, zircon, bismuth, bismuthinite, emplectite, hodrušite, and the sulfotellurides joséite-A, joséite-B, tetradymite and ingodite. Early bismuth is replaced by abundant bismuthinite, which also locally contains symplectitic intergrowths of emplectite (Cu1.02Bi 0.98S2.00). A single euhedral crystal of hodrušite [(Cu4.04Fe0.12Ag0.03)Σ 4.19(Bi5.87Pb0.02)Σ5.89S 10.92] has Pb-bearing tips that contain 3.62 to 4.39 wt.% Pb (0.33 to 0.40 apfu respectively). Joséite-A (Bi4.04Te 0.95S2.01) forms an intergrowth with ingodite, enclosed in emplectite. Joséite-B (Cu0.02Bi4.01Te 1.93S1.04) is intergrown with joséite-A and with bismuthinite in emplectite. Tetradymite [(Bi2.00Cu 0.02)Σ2.02Te1.95S1.03] is included in emplectite and bismuthinite. Ingodite is usually enclosed in bismuthinite as very small grains with a composition Bi1.98Te 1.00S1.02. Late-stage or supergene alteration of this association generated fairly abundant bismutite and rare bismite. On the basis of experimental data, the equilibrium association of bismuth, bismuthinite, emplectite and hodrušite, typical of hydrothermal ore deposits but uncommon in granitic pegmatites, is restricted to relatively low temperatures and a pressure in the range 2-3 kbar.